Pericardial effusion in status epilepticus and global developmental delay one-year-old patient with co-exist of atrial septal defect: a case report - Pradhika Perdana Sakti; Ariani (Pediatric Sciences Journal, 2022)
Introduction: Atrial septal defect (ASD) is one of the most common types of congenital heart disease (CHD) and occurs due to spectrum closure failure during the intrauterine period. ASD is generally asymptomatic, but it can affect patients from various aspects. Case presentation: A 1-year-old 4-month-old girl was referred with a major complaint of shortness of breath as early as 6 days before hospital admission. The dullness accompanied by a fever disappears, as convulsions, pallor and vomiting. On physical examination, a positive result in pathological reflex was found in a decrease in consciousness, epicantal fold, conjunctiva and pale skin, and edema of the left limb. The patient was examined for echocardiography and found the presence of moderate primum ASD with a left to the right pyre, mild tricuspid regurgitation with the possibility of pulmonary hypertension, and effusion pericardium with the collapse of the right atrium. In the laboratory results show the presence of normochromic normocytic anemia, leukocytosis, mild hyponatremia, hypokalemia, hypocalcemia, hypophosphatemia, increased PCT, increased SGOT / SGPT, PT elongation, a decreased of free T4 and increase in TSH, IgG CMV (+), IgG toxoplasma (+), IgG HSV-1 (+), IgG HSV-2 (+), and IgG Rubella (+). The patient is given treated at the PICU and provided with the help of ventilation, antibiotics, antipyretics, anticonvulsants, inotropic, and sympathomimetic agents. On the ninth day of care, the patient experienced cardiac arrest. RJP was performed, but the patient did not have ROSC and was pronounced dead. Conclusion: ASD affects the patient's condition as well as the patient's survival both directly and indirectly. There is a link between ASD and developmental disorders, pericardial effusion and patient mortality. It is necessary to conduct a comprehensive evaluation and management of patients with ASD.